Assessment of disease severity in hospitalized community-acquired pneumonia by the use of validated scoring systems - Sandleen Iftikhar; Bjørn Waagsbø (BMC Pulmonary Medicine)
Abstract Background Severity assessment of community-acquired pneumonia (CAP) is essential for many purposes. Among these are the microbiological confirmation strategy and choice of empirical antimicrobial therapy. However, many severity assessment systems have been developed to aid clinicians to reach reliable predictions of severe outcomes. Methods We aimed to apply nine disease severity assessment scoring systems to a large 2016 to 2021 CAP cohort in order to achieve test sensitivity, specificity and predictive values. We used intra-hospital all-cause mortality and the need for intensive care admission as outcomes. The area under the receiver operating characteristic (ROC) curve was used to display test performance. Results A total of 1.112 CAP episodes were included in the analysis, of which 91.4% were radiologically, and 43.7% were microbiologically confirmed. When intra-hospital all-cause mortality was set as outcome, tests designed for CAP severity assessment, like PSI, and CURB65 outperformed the more generic systems like NEWS2, qSOFA, SIRS and CRB65. Designated tests for CAP (PSI, IDSA/ATS and CURB65) and overall critical illness (SOFA) displayed acceptable performances as compared to non-specific tests. Comparable results were gained when intensive care admission was set as outcome. The area under the receiving operating curve was 0.948, 0.879, 0.855 and 0.726 for the SOFA, PSI, IDSA/ATS and CURB65 scoring systems, respectively. Conclusion CAP severity assessment remains important. Designated CAP severity assessment tools outperformed generic tests.